2018
DOI: 10.1016/j.bpj.2017.11.1811
|View full text |Cite
|
Sign up to set email alerts
|

Dual Biomembrane Force Probe Enables Single-Cell Mechanical Analysis of Signal Crosstalk between Multiple Molecular Species

Abstract: Conventional approaches for studying receptor-mediated cell signaling, such as the western blot and flow cytometry, are limited in three aspects: 1) The perturbing preparation procedures often alter the molecules from their native state on the cell; 2) Long processing time before the final readout makes it difficult to capture transient signaling events (<1 min); 3) The experimental environments are force-free, therefore unable to visualize mechanical signals in real time. In contrast to these methods in bioch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…More recently, the dual biomembrane force probe (dBFP) has been developed, which allows examination of the signal reception, initiation, and transduction from one receptor to another on a single cell step by step in space and time. It has demonstrated that the mechano-signals induced by TCR–pMHC and GPIbα–VWF lead to the up-regulation of integrin functions on a T-cell and a platelet, respectively ( Ju et al. , 2017 ).…”
Section: Nanotools For Studying Receptor-mediated Cell Mechanosensingmentioning
confidence: 99%
“…More recently, the dual biomembrane force probe (dBFP) has been developed, which allows examination of the signal reception, initiation, and transduction from one receptor to another on a single cell step by step in space and time. It has demonstrated that the mechano-signals induced by TCR–pMHC and GPIbα–VWF lead to the up-regulation of integrin functions on a T-cell and a platelet, respectively ( Ju et al. , 2017 ).…”
Section: Nanotools For Studying Receptor-mediated Cell Mechanosensingmentioning
confidence: 99%
“…The reporter BFP consisted of a micropipette aspirated human red blood cell with a glass bead coated with annexin V attached to its apex via biotin-streptavidin coupling. [41][42][43] An opposing micropipette aspirated a platelet and was driven by a piezoelectric translator to move forward/backward to get in/out of contact with the annexin V bead to test for binding. The horizontal position of the bead was tracked by a high-speed camera, which reflected the red blood cell axial deformation.…”
Section: Dual Biomembrane Force Probe Assaymentioning
confidence: 99%
“…Inhibition of the GPIb-triggered Ca 2+ prevents platelet firm adhesion, suggesting that Ca 2+ is an obligatory signaling molecule on the pathway to GPIIb/IIIa activation 8 9 61 62. Although how the transmission of the mechanical signal across the membrane and its transduction into cytoplasmic chemical signals are fulfilled remains elusive, a juxtamembrane mechanosensitive domain (MSD) in the GPIbα subunit was found to correlate with intraplatelet Ca 2+ triggering (figure 1): force-induced MSD unfolding is well correlated with an α-type Ca 2+ signal8 9 and the subsequent GPIIb/IIIa intermediate activation, whereas failing to unfold MSD will most likely result in β-type or null-type Ca 2+ signals and limit GPIIb/IIIa activation 60 63. Intracellularly, a scaffold protein that binds to GPIb cytoplasmic tail, 14-3-3ζ, was also found to play a pivotal role in GPIb mechanosignaling (figure 1), as the inhibition of 14-3-3ζ–GPIb association strongly inhibited GPIb-triggered Ca 2+ flux and subsequent GPIIb/IIIa activation 60 64.…”
Section: Introductionmentioning
confidence: 99%